(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses the relevance of the study of the formation of the readiness of future teachers for innovative activities using the cluster method. The characteristics of the basic concepts "health", "general physical development", "development of sports and health-improving clusters" are given from the standpoint of different authors. The components of students’ readiness for innovative activity are considered, the types of software that are used in the university in preparing students are described.